Penerapan Lean Development pada Pengembangan Aplikasi Client-Server untuk Import Data yang Dinamis - Jayadi, Puguh (Jurnal Manajemen Sistem Informasi (JMASIF), 2023)
Developing an application that suits the initial needs and still considers the efficiency side of the application sometimes makes the development schedule longer and the process convoluted. The research conducted applies Lean Development to improve the efficiency of software development with a case study of client-server applications. The identified issue is the handling of large and dynamic Excel data imports into MySQL that can slow down application performance. The purpose of this research is to modify the Lean Development method to reduce waste and improve the quality of development and implementation of data import applications. The research methods involved include requirements analysis, application design, prototype development, and performance testing. Experiments show that the developed application is able to achieve 100% conformity in the testing of the assigned features. The results show Lean Development to improve the development of small-scale applications with dynamic data loads through the reduction of valueless activities and improving software quality.